Implementation of Islamic-Based Learning at Al-Madaniyah Samuda Integrated Islamic Senior High School - Ahmad Akwan; Muhammad Tri Ramdhani (Jurnal Hadratul Madaniyah, 2026)
Islamic-based learning is an educational approach that emphasizes the integration of Islamic values into the entire learning process, including planning, implementation, and evaluation stages. This study aims to describe and analyze the implementation of Islamic-based learning in the Akidah Akhlak subject at Al-Madaniyah Samuda Integrated Islamic Private Senior High School (SMAS IT Al-Madaniyah Samuda). The focus of the study is directed toward the learning planning process, learning implementation, learning evaluation, as well as supporting and inhibiting factors in its implementation. This research employs a qualitative approach with a field research design. Data were collected through observation, in-depth interviews, and documentation, while data analysis was conducted using data reduction, data presentation, and conclusion drawing techniques. The results indicate that Islamic-based learning at SMAS IT Al-Madaniyah Samuda has been systematically integrated into lesson planning through the preparation of instructional tools that internalize Islamic values. The implementation of Akidah Akhlak learning is carried out using contextual approaches, role modeling, and habituation, supported by the use of the classical text Akhlāqul Lil Banīn as the main reference. Learning evaluation is not only oriented toward cognitive aspects but also includes affective and psychomotor aspects of students. The main supporting factors include teacher competence, a religious school culture, foundation support, and continuous religious habituation. Meanwhile, inhibiting factors consist of limited instructional time, differences in students’ abilities, and the influence of the family environment. This study contributes to enriching the body of knowledge in Islamic education, particularly regarding the implementation of Islamic-based learning at the secondary school level.